Reviving Local Heritage: Leadership in Building a Culture of Quality - Daryanto, Daryanto; Carwa, Carwa; Astuti, Ida Yuli; Munawar, Aris; Kholisoh Nuryani, Lilis (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This study analyzes leadership preferences in building a quality culture based on local wisdom in schools. The research method used is a qualitative case study approach involving in-depth interviews, participant observation, and document analysis. The data analysis technique used is thematic analysis, which includes systematic data coding, grouping similar codes, and drawing conclusions based on identified themes. The study results indicate that inclusive and supportive leadership strategies and the integration of local wisdom in teaching materials have succeeded in increasing student engagement in learning and strengthening their character. In addition, the findings show that the support of the principal in the form of policies and initiatives plays an essential role in the successful implementation of local wisdom-based programs. The implication of this study is the importance of school leadership in encouraging and supporting local culture-based programs to achieve more holistic and sustainable education.